Characteristics of Salmonella From Chinese Native Chicken Breeds Fed on Conventional or Antibiotic-Free Diets - Cui, Lulu; Liu, Qingxiao; Jiang, Zhiyu; Song, Yan; Yi, Shoujing; Qiu, Jianhua; Hao, Guijuan; Sun, Shuhong (Frontiers in Veterinary Science, 2021)
Salmonella is a common food-borne Gram-negative pathogen with multiple serotypes. Pullorum disease, caused by Salmonella Pullorum, seriously threatens the poultry industry. Many previous studies were focused on the epidemiological characteristics of Salmonella infections in conventional antibiotic use poultry. However, little is known about Salmonella infections in chicken flocks fed on antibiotic-free diets. Herein, we investigated and compared Salmonella infections in three Chinese native breeders fed on antibiotic-free diets, including the Luhua, Langya, and Qingjiaoma chickens, and one conventional breeder, the Bairi chicken, via analyzing 360 dead embryos in 2019. The results showed that the main Salmonella serotypes detected in a total of 155 isolates were S. Pullorum (82.6%) and S. Enteritidis (17.4%). Coinfection with two serotypes of Salmonella was specifically found in Bairi chicken. The sequence type (ST) in S. Pullorum was ST92 (n=96) and ST2151 (n=32), whereas only ST11 (n=27) was found in S. Enteritidis. The Salmonella isolates from three breeder flocks fed on antibiotic-free diets exhibited phenotypic heterogeneity with a great variety of drug resistance spectrum. Most of the isolates among three chicken breeds Luhua (64.9%, 50/77), Langya (60%, 12/20) and Qingjiaoma (58.3%, 7/12) fed on antibiotic-free diets were resistant to only one antibiotic (erythromycin), whereas the rate of resistance to one antibiotic in conventional Bairi chicken isolates was only 4.3% (2/46). The multidrug-resistance rate in Salmonella isolates from layer flocks fed on antibiotic-free diets (20.2%, 22/109) was significantly (P<0.0001) lower than that from chickens fed on conventional diets (93.5%, 43/46). However, high rate of resistance to erythromycin (97.4%~100%) and streptomycin (26%~41.7%) were also found among three breeder flocks fed on antibiotic-free diets, indicating resistance to these antibiotics likely spread before antibiotic-free feeding in poultry farms. The findings of this study supplement the epidemiological data of salmonellosis and provide an example of the characteristics of Salmonella in the chicken flocks without direct antibiotic selective pressure.